Educational process for people with autism spectrum disorder from the analysis of scientific production available in SciELO - Brazil (2005-2015) - Fabiana Ferreira do Nascimento; Mara Monteiro da Cruz; Patricia Braun (Arizona State University, 2016)
Access to the school, the guarantee of permanence and promotion of learning, regardless of the student's conditions, is the duty of the state and family who share responsibility for the educational process, which means the school learning of the individuals. Lack of knowledge about autism spectrum disorder (ASD) and inadequate conditions of physical space, lack of resources and curricular adaptations may compromise success in the school history of the students with the characteristics of this disorder in their development. Faced with these issues, this research aimed to map and analyze the state of the art about the schooling process of this individual over a decade, available in Scientific Electronic Library Online (SciELO-Brazil). The choice of this database was to be a broad range of space, easy and free access to indexed journals and recognized academically, revealing a rich source of search that could be used to access knowledge by teachers of basic education. The time frame was due to being a period in Brazil where there was the approval of various legal regulations for school inclusion, specific for students with ASD. From the mapping and analyses we found, among other things, that there are few studies that investigate the process of education and especially the organization and implementation of strategies or classroom resources with this student.